An Empirical Study on the Determinants of Dividend Policy in the UK - zhuang, xiaofei (2012)
The objective of this study is to find out the determinants of dividend policy in the UK for the non-financial companies in the year from 2002 to 2011. The dividend policy is one of the most debatable issues in the corporate finance literature and still keeps its prominent place both in developed and emerging markets. Dividend policy is one of the most intriguing topics in financial research. Even now, researchers still have enthusiasm to solve the dividend puzzle, resulting in a large number of hypotheses, theories and explanations. Among the researches in the area of dividend policy, the determinant of it is most popular.